A bibliometric snapshot on artificial intelligence in education / Ir Dr Amirul Abd Rashid - Abd Rashid, Amirul (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The term “Artificial Intelligence” (AI) was coined by John McCarthy in 1956 during the Dartmouth Conference. Since then, numerous researchers, scientists, and innovators have contributed to the advancement and popularization of AI in almost all aspects of human life. Likewise, the education sector has leveraged the advancement of computer technology since the mid-1900s. The developments in computers and related computing technologies have led to a rise in the use of computers in different parts of the education sector, such as the development of computer aided instruction and learning in classroom interactions. Later developments in computers and computer-related technologies, including networking, the internet, the world wide web, and increased capabilities processing, computing, and task-oriented programs and software packages, have led to the increased application of computers in different ways in the education sector. Computer and information communication technologies have continued to evolve over the years, leading to the development of AI. According to Coppin, AI relates to the ability of machines to adapt to new situations, deal with emerging situations, solve problems, answer questions, devise plans, and perform various other functions that require some level of intelligence that is typically evident in human beings.